The Jews of Poland; a social and economic history of the Jewish community in Poland from 1100 to 1800 - Weinryb, Bernard D. (Philadelphia, Jewish Publication Society of America, 1973)
This study was commissioned by the committee on Linguistic in documentation of the federation International de documentation. it is concerned with the linguistic aspects of infprmation science, and in particular with the linguistic components of document analysis, descriptive, and retrieval.
Bibliography: p. [403]-409.
aia 21/6/17
Loans
Keywords: Jews